Return to Competitive Play After Hamstring Injuries Involving Disruption of the Central Tendon. (January 2013) - Comin, Jules; Malliaras, Peter; Baquie, Peter; Barbour, Tim; Connell, David
Background: The hamstring muscles are the most commonly injured muscle group in many different sports. Recovery time is often unpredictable and prolonged, and recurrent injury is common. Hypothesis: Hamstring injuries that disrupt the central tendon enclosed within the muscle belly require a longer recovery time than do injuries involving only muscle, epimysial fascia, or the musculotendinous junction. Study Design: Cohort study; Level of evidence, 3. Methods: Injury records from professional sports teams were reviewed to determine the length of recovery from each hamstring injury that occurred over a 24-month period. The integrity of the central tendon on magnetic resonance imaging (MRI) was retrospectively reviewed for each case. The association between central tendon disruption on MRI and recovery time was determined. Results: There were 62 hamstring injuries included for analysis; 45 (72%) involved the biceps femoris, 11 (18%) involved the semimembranosus, and 6 (10%) involved the semitendinosus. Central tendon disruption was identified in 12 (45%) of the biceps femoris injuries and in none of the injuries to the other 2 muscles. Three of these injuries were treated surgically, with a median recovery time of 91 days. The median (interquartile range [IQR]) recovery times for those remaining biceps femoris injuries with and without central tendon disruption were 21 days (IQR, 9-28) and 72 days (IQR, 42-109), respectively ( P < .01). Conclusion: Disruption of the central tendon in injuries to the biceps femoris results in a significantly longer recovery time than injuries that do not disrupt the central tendon. This highlights the distinction between injury to the hamstring muscle and injury to the hamstring tendon, which is underappreciated as being a distinct entity when injury involves the enclosed central portion of the tendon.